A kinematically enhanced constitutive model for elastic and inelastic analysis of unidirectional fibre reinforced composite materials. (June 2017) - Vu, Van D.; Sheikh, Abdul Hamid; Nguyen, Giang D.; Shen, Luming
Abstract: A constitutive model with an enhanced strain field is developed in this study for predicting the behaviour of unidirectional fibre reinforced composite materials. The different deformation modes introduced in the enhanced strain field take into account of both the variation of strains and internal equilibrium conditions across the fibre-matrix interfaces in unidirectional composites. This opens rooms to accommodate the difference in the responses of fibre and matrix and allows both fibre and matrix to be represented separately by their own constitutive responses. The enriching deformation modes and internal equilibrium conditions lead to a combination of both upper and lower bound solutions on different components of the stress/strain tensors, resulting a homogenised macro response that compares well with experimental data and sophisticated homogenisation approaches in the literature. In addition, the key feature of the proposed approach is that the macro homogenised behaviour can be written in terms of incremental responses of both constituents and their interactions, facilitating the applications in both linear and nonlinear regimes of behaviour of both fibre and matrix. In parallel with this, a new coupled damage-plasticity model is also developed for the matrix behaviour and validated against experimental data of two resins, before being used in the proposed approach. The performance of the model and its promising features are demonstrated through verification with existing benchmarking models and validation with experimental data in both elastic and inelastic regimes. Graphical abstract: Highlights: Kinematic enhancement leads to better modelling of fibre reinforced composites. The strain field is enhanced with different modes of deformation. This allows accommodation of the difference in fibre and matrix responses. The responses of fibre and matrix are linked through a homogenisation scheme. This gives better predictions of both effective properties and nonlinear responses.